46.4k views
5 votes
Solve for x2x^2 + 12x-32=0

User Manta
by
7.9k points

1 Answer

4 votes

If we have an equation with the form:


ax^2+bx+c=0

The solutions of the equation are:


\begin{gathered} x_1=(-b+√(b^2-4ac))/(2a) \\ x_2=(-b-√(b^2-4ac))/(2b) \end{gathered}

So, if we replace a by 2, b by 12, and c by -32, we get that the solutions of the equation are:


\begin{gathered} x_1=(-12+√(12^2-4\cdot2\cdot(-32)))/(2\cdot2)=2 \\ x_2=(-12-√(12^2-4\cdot2\cdot(-32)))/(2\cdot2)=-8 \end{gathered}

So, the solutions are x=2 and x=-8

Answer: x=2 and x= -8

User Mejwell
by
8.0k points